Development of Islamic Education: The Multidisciplinary, Interdisciplinary and Transdisciplinary Approaches - Dina Mardiana; Abd. Rahim Razaq; Umiarso Umiarso (Al-Hayat Al-Istiqomah Foundation, 2020)
In the ideal level, Islamic education must touch on 3 (three) aspects.